Publication activity of Russian university students - N. V. Shabrova; P. A. Ambarova (Образование и наука)
Introduction. An investigation of student publication activity is an important element of the study of their research culture. The authors’ attention is focused on student publications in highly ranked journals reflecting the involvement of students in “adult” university science and making a serious contribution to it. A research on student publication activity is attracting considerable interest due to its significance for university scientific and educational practices, whereas this issue is not closely examined in theoretical and empirical terms.Aim. The present paper aims to consider the features of the publication activity of students of Russian universities in the segment of highly ranked journals. It is revealed by solving the following research issues: evaluation of students’ attitude to publication activity; characterisation of quantitative indicators of students’ publication activity in highly ranked journals; identification of the specifics of students’ publication activity depending on belonging to different fields of scientific knowledge, level of training and other indicators.Methodology and research methods. The article presents the results of an empirical study conducted in 2023 using the methods of an online survey of students of Russian universities localised in all federal districts (n = 3032 people), as well as applying content analysis of highly rated journals (indexed in RSCI, WoS, Scopus). The results and conclusions of the authors’ research are compared with Russian and foreign studies on similar topics.Results. The main results of the study are the characteristics of the place of publication activity in the general structure of students’ research activities. Despite the fact that the preparation of articles is one of the most popular forms of research, it is shown that a small number of students are involved in youth science on a permanent basis. It is concluded that the authors of publications in highly ranked journals represent a special group of students, distinguished by cognitive and motivational readiness for such activities.The article presents the features of the publication activity of a selected group of students: genderasymmetry (predominance of female students among authors); multiple authorship; an increase in the degree of publication activity from junior to senior courses, from bachelor’s degree (specialty) to master’s degree. The question of the ethical side of student publications is discussed. It is justified as a promising area of research.Various factors of success of student publications in the segment of highly ranked journals are discussed. The factors are as follows: involvement in research practices on a regular basis, the presence of a scientific mentor. In conclusion, the possibilities of using various theoretical frameworks for interpreting the publication activity of students are considered.Scientific novelty of the research consists in the introduction into scientific circulation of new empirical data representing the all-Russian situation with the publication activity of students of the first two levels of education (bachelor’s/specialist’s and master’s degree), as well as their interpretation in a comparative perspective with foreign studies.Practical significance of the article is the possibility of using the results and conclusions of the current study in the development of university programmes for involving students in research and scientific mentoring.